Investigating Online Learning by Using Google Classroom in the Covid-19 Pandemic - Diana Zuriati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2022)
During the covid-19 pandemic, the researcher needs to assess online learning by using Google classroom for English for Foreign Language students. Since online learning differs from face-to-face learning, the researcher is interested in doing this study. Online learning is learning process that students and the teacher is not in one classroom in the same place but in one medium in different place. The aim of the research is about online learning for English for Foreign Language students during the covid-19 pandemic at Sekolah Tinggi Bahasa Asing (STBA) Persada Bunda. In this study, descriptive research was carried out. The questionnaire, which was provided in Google form, was filled up by 21 English for Foreign Language students at random. To collect data, the students were requested to complete a questionnaire with 20 questions. After that, the researcher analyzed the data using a questionnaire regarding online learning by using Google classroom in the Covid-19 pandemic. The result of the research was in positive response of choosing “strongly agree” and “agree”. In conclusion, using Google classroom was one of the effective medium in online learning since there were some benefits to solve the learning process even though online learning by using Google classroom was less effective than face-to-face learning.